Lithosiini and Arctiini of Daghestan (NE Caucasus) (Lepidoptera: Erebidae, Arctiinae) - Dubatolov, V. V.; Poltavsky, A. N.; Iliyna, E. V. (SHILAP Revista de lepidopterología, 2021)
16 species of Lithosiini and 25 species of Arctiini (Erebidae: Arctiinae) are recorded from Daghestan, North-East Caucasus. Nine Lithosiini species and one Arctiini species (Katha depressa (Esper, 1787), Manulea pygmaeola (Doubleday, 1848), M. lurideola (Zincken, 1817.), Cybosia mesomella (Linnaeus, 1758), Eilema caniolum (Hübner, [1808]), Atolmis rubricollis (Linnaeus, 1758), Pelosia muscerda (Hufnagel, 1766), Setina roscida ([Denis & Schiffermüller], 1775), Thumatha senex (Hübner, [1808]), Epatolmis caesarea (Goeze, 1781) were formerly not known from Daghestan territory. Localities, typical biotopes and imago flight period are provided for all species.